A HERMENÊUTICA DA EDUCAÇÃO AMBIENTAL E O PARADOXO DA SUSTENTABILIDADE - Córdula, Eduardo Beltrão de Lucena (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611706670 Contemporary society is currently seeking to reverse the severe damage to the planet, and thatdirectly affect our way of life, the global environmental and disorders that bring as a consequence,damage to life forms. This paradigm is due to a perceived social and environmental dichotomized,that even with the emergence of Environmental Education in the 60’s, in its 50 years of operation,some managed to change the vision of man about himself and about this planet, generating a race"green" development still far from ideal, which brought about a false-sustainability, aiming onlythe preservation and conservation of natural resources. However, with the Hermeneutics alliedenvironmental issues, has launched a new look for the interpretation of the phenomena on thisplanet, bringing awareness to the genesis of awareness of the real changes necessary to humansand their actions cork planet, uniting society and environment through the environmentalEducation for taking a sustainable development now, aiming thus environmental quality of life forthese and future generations